Improving Happiness of The Elderly through Virtual Reminiscence Intervention - Seda, Adventia Emilia Krysna Sipi; Halim, Magdalena Surjaningsih (Psympathic : Jurnal Ilmiah Psikologi, 2024)
Happiness is an important variable in improving the physical and psychological well-being of the elderly. An effective intervention to enhance the variable is reminiscence. Therefore, this research aimed to evaluate the impact of virtual reminiscence intervention on the happiness of the elderly. The method used was quasi-experimental with a pre-test and post-test design as well as a non-equivalent control group. The sample consisted of 7 and 8 participants in experimental and control groups, aged 60-74 years. In addition, purposive sampling method was used to select participants from 3 nursing homes in Yogyakarta. Data was also collected using Oxford Happiness Questionnaire (OHQ), Happy Emotion Thermometer Scale, interviews, and observations. The results showed a significant difference between control and experimental groups on OHQ and Happy Emotion Thermometer scales. According to qualitative evaluation, the intervention generated positive feelings and reduced negative emotions. In this context, virtual reminiscence intervention sessions played a role in increasing the happiness of the elderly.